A descriptive analysis of film music enthusiasts' purchasing and consumption behaviors of soundtrack albums: An exploratory study. (May 2016) - Keown, Daniel J.
While a substantial body of research has explored purchasing and consumption behaviors of music consumers, relatively less attention has been devoted toward understanding these behaviors among specific populations of music enthusiasts and sound recording collectors. Using a researcher-designed survey, this exploratory study examined film music enthusiasts' purchasing and consumption behaviors regarding soundtrack albums. This research indicated no significant differences on whether soundtrack albums were purchased before or after viewing the film of the soundtrack ( p > .05). Specifically, some of the most frequent factors reported for purchasing soundtrack albums among film music enthusiasts were based on the composer, watching the film, desire of owning the newly expanded/extended/remastered/reissued edition, and limited pressings/low quantities available for purchase. Findings suggest that film music enthusiasts seem to base soundtrack purchasing decisions on a variety of factors. These purchasing attributes, unique to film music enthusiasts and album collectors, will be discussed in relation to film music record producers', critics', and collectors' assumptive theories and perspectives.